Public versus Private Ownership : The Current State of the Debate - Shirley, Mary; Walsh, Patrick (World Bank, Washington, DC, 2014)
At the heart of the debate about public versus private ownership lie three questions: 1) Does competition matter more than ownership? 2) Are state enterprises more subject to welfare-reducing interventions by government than private firms are? 3) Do state enterprises suffer more from governance problems than private firms do? Even if the answers to these questions favor private ownership, the question must still be asked: Do distortions in the process of privatization mean that privatized firms perform worse than state enterprises? The author's review found greater ambiguity about the merits of privatization and private ownership in the theoretical literature than in the empirical literature. In most cases, empirical research strongly favors private ownership in competitive markets over a state-owned counterfactual (although construction of the counterfactual is itself a problem). Theory's ambiguity about ownership in monopoly markets seems better justified. Since the choice confronting governments is between state ownership and privatization rather than between privatization and optimality, theory has left a gap that empirical work has tried to fill. Further research is needed.